THEORETICAL BASIS OF PARAMETRIC SYNTHESIS FOR CARRYING SYSTEMS OF CARS - Fomin, O. V.; Gorobchenko, O. M.; Kocheshkova, N. S.; Kovalenko, V. V. (Science and Transport Progress, 2017)
Purpose. The article is aimed to systematize and structure representation of theoretical grounds for the optimization designing of railway car components and practical ways of its implementation. Methodology. The study is based on analysis of several well-known articles on the subject, as well as on authors' researches, some mathematical foundations and computer modeling. The rolling stock components structural analysis was made by applying modern and acknowledged methods. Findings. In the study the authors systematized the set of methodological approaches to the freight car design processes; they also analyzed every application phase of the designing process and its conditions. The article presents the developed mathematical model of the car component implementation. This model takes into account all the calculated cases of the car life cycle. Moreover, the model also can be applied to other transport modes accounting their specific operation modes. The possibility to generate different construction options for equally strong car component with minimum material intensity was also shown in the article. There were several methods developed for finding optimal solutions that make it possible to calculate the sought characteristics of construction elements with the reliable accuracy. The presented variety of different approaches significantly extends engineering apparatus by increasing the synthesis and analysis abilities of the car design. Originality. The authors proposed the methodological foundations of the car components design aimed at creating their optimal structural parameter execution and the operating features based on the results of the detailed research. Practical value. Expediency and effectiveness of the presented methods has been confirmed by positive experience of its application when constructing the general-purpose gondola cars, models 12-9904 and 12-9904-01, as well as when upgrading existing constructions of freight cars, model 12-9745 and the hoper car 20-9749.